The Effect of AIDS Stigmatization on Curing Patients and Physician- HIV/AIDS Patient Relationship: Stigmatization of Patients with HIV/AIDS - Tavakol , Mohammad; Nikayin, Diba; Rezaei , Masoomeh (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: HIV/AIDS and its carrier are not only known as a disease and a patient, respectively. Since the transmission of the disease is most relevant to human deviant behavior, a stigma against the disease has been formed. This study seeks to examine the effect of the stigmatization of the disease imposed on the treatment process and interaction between the physician and HIV/AIDS-positive patient in Iranian society. Materials and Methods: A qualitative research method has been used in this study. Data collection has been carried out through interviews. Depth interviews and semi-structured interviews have been employed for the patients and doctors respectively. This study was done in the consultation center and infectious disease ward of Imam Khomeini hospital. Six clients of the consultation center and seven infectious disease specialists were selected. Ethical Considerations: The study followed standard ethics guidelines concerning informed consent and confidentiality. Findings: HIV/AIDS-related stigma has sparked illogical fears, affects physician-patient interaction in the medical community, and has led to discrimination among these patients in many cases in terms of the right to treatment. Conclusion: The results obtained showed the unfavorable impacts of the AIDS-related stigma imposed on the medical community and this is an obstacle facing patients with HIV/AIDS to achieve equal treatment rights. The results of the present study show the role of stigma in converting this disease into a socio-cultural phenomenon. Physicians, like other members of society, are affected by values, norms and are constructs of society. *Corresponding Author: Mohammad Tavakol; Email: mtavakol@ut.ac.ir; ORCID: https://orcid.org/0000-0001-7300-2814 Please cite this article as: Tavakol M. Nikayin D. Rezaei M. The Effect of AIDS Stigmatization on Curing Patients and Physician- HIV/AIDS Patient Relationship. Bioeth Health Law J. 2021; 1:1-9: (e8). http://doi.org/10.22037/bhl.v1i1.38133